Hubungan Kadar Vitamin D Plasma dengan Indeks Mitosis pada Pasien Kanker Payudara - Pratiwi, Astrid Siska; Siregar, Yahwardiah (Fakultas Kedokteran Universitas Sriwijaya, 2018)
Breast cancer is the most common cancer suffered by women and one of the biggest causes of death for women worldwide. Later, nutrition became one of the risk factors in breast cancer outcome, one of them is vitamin D. Calcitriol is the active form of vitamin D as an anti-proliferation, and inhibits tumor growth. Uncontrolled proliferation is one of the characteristics of cancer cells. Tumor growth rates become prognostic markers that can be evaluated by correlating at cellular levels such as mitosis. The aimed of this study was to analyze the relationship between vitamin D levels and mitosis index in breast cancer patients. Research with cross sectional design gathered 50 breast cancer patients who were newly diagnosed and had never received chemotherapy. The study was conducted from January 2017 - August 2018 at the Department of Surgical Oncology, RSUPH. Adam Malik Medan. Examination of plasma vitamin D levels is done by ELISA technique at the Lab. Faculty of Medicine Universitas Sumatera Utara. The mitosis index data was obtained from the medical record of the research subjects reviewed by anatomical pathology specialists at the Lab. Anatomical Pathology of Faculty of Medicine Universitas Sumatera Utara. Statistical test uses Fisher Exact. The results of the study 48% of subjects had vitamin D sufficiency, 38% insufficiency and 14% had deficiency. The mean vitamin D levels in all of the study subjects were insufficiency (27.93ng / ml). In this study there was no significant relationship between plasma vitamin D levels and mitosis index in breast cancer patients p = 0.062. The insignificant relationship between vitamin D levels and mitotic index in this study shows that vitamin D not a single factors to influence the mitosis index in breast cancer patients.